ChemInform Abstract: Broadly Applicable Z‐ and Diastereoselective Ring‐Opening/Cross‐Metathesis Catalyzed by a Dithiolate Ru Complex. Issue 32 (12th August 2014) - Koh, Ming Joo; Khan, R. Kashif M.; Torker, Sebastian; Hoveyda, Amir H.
Abstract All the products are obtained with excellent (Z)‐selectivities.